Reducing Cognitive Load in Sales Training: An Experimental Study on Self-Directed Learning - Edén,Linnéa (2025)
This thesis examines how insights from cognitive science can inform the design of self-study training materials to reduce cognitive load and enhance sales onboarding in complex technical domains. The study was conducted at a global company specializing in industrial sensor solutions, focusing on machine vision sales training. The study was conducted in three phases. First, a pre-study mapped the sales current onboarding experience. High cognitive load, caused by the volume, structure, and content presentation emerged as a key challenge. Based on these findings, Cognitive Load Theory, Schema Theory, and Cognitive Theory of Multimedia Learning were selected as theoretical frameworks to guide the following phases. In phase two, a machine vision overview training module was analyzed and redesigned into two e-learning versions: a control and an experimental version. The latter was optimized for extraneous cognitive load reduction and schema formation. In phase three, an experiment (N = 25) tested the design intervention’s impact on knowledge gain and perceived cognitive load. The experimental group reported significantly lower extraneous load and showed a trend toward greater knowledge gains, especially on difficult items. They also reported slightly higher motivation and confidence, though differences were not statistically significant. The thesis further discusses broader cognitive challenges in the onboarding journey, including fragmented content, poor navigation, lack of overview modules, and non-situated learning. It also of ers actionable recommendations to the company for improving the learning experience for new salespeople. The study aims to demonstrate the practical value of applying cognitive science to corporate training design.
Keywords: Cognitive Science; Cognitive Load Theory; Schema Theory; Instructional Design; E-learning; Self-Study Materials; Multimedia Learning; Sales Onboarding